THE ACTIVITIES OF EARLY KYRGYZ HISTORICAL FIGURES ON THE EXAMPL OF MOURNING SONGS IN THE 19th - 20th CENTURIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The state of the state of the Kyrgyz people in the XIX - early. The 20th century isone of the most vague moments in our history. In Soviet historiography, the history of the stateof the majority of peoples was treated superficially, so this situation was mostly not disclosed.Moreover, since the study of the history of nomads in the past was dominated by a Eurocentricview, there are erroneous views that during this period the Kyrgyz people were divided into tribesand could not pursue a single state policy and did not become the sovereign of their own state. Ofcourse, at that time, the vast majority of the Kyrgyz led a nomadic lifestyle, but their oral creativityand culture, passed down from generation to generation, is priceless. This article (Kokon Khanateand the periods of the colonial policy of Russia) reflects the activities of famous people duringthe period of the Kokon Khanate (19th century): Medet Datka, Taylak baatyr, Nuzup Biy, OrmonKhan, Alymbek Datka, Alymkul Lashker reflected in the folk oral produced cats of the Kyrgyz asfolklore source. Prominent representatives of the Kyrgyz community who lived during the periodof Russian colonial policy (early twentieth century): Kurmanzhan Datka, Borombay Biy, ShabdanBogatyr, Iskhak Asan uulu, Mamyr Mergen uulu, Abdyldabek, Moldo Ashir and other activities ofindividuals, historical events, national The liberation struggle was reflected in the sources of oralworks that were passed down from generation to generation.
Keywords: Kokon Khanate, Russian kingdom, lamentations, historical figures, liberation, statehood, folklore.